NAVIGATING THE INFORMATION LANDSCAPE: A DESCRIPTIVE STUDY OF INFORMATION NEEDS AND PREFERENCES AMONG HOSPITALITY MANAGEMENT UNDERGRADUATES IN MALAYSIA - Mohd Hazrin Iman Noorkhizan; Malissasahila Abdul Manap; Jazira Anuar; Azlina Samsudin; Wan Nor Bayah Wan Kamarudin; Mohamad Amiruddin Mohamad; Mohamad Amiruddin Mohamad (Journal of Islamic, Social, Economics and Development, 2024)
This study investigates the information needs of undergraduates of Hotel and Tourism Management in a Public University. Conducted through an online survey, the research examines hospitality management students' preferences for information sources, methods of information gathering, and preferred materials. Noteworthy findings indicate that students actively seek information for their future careers, driven by both job search and academic pursuits. Language acquisition, particularly in English and a third language, emerges as a priority. The internet is the primary information source, encompassing details about post-graduation job opportunities. Students express satisfaction with institutional facilities and information provisions. The study recommends prioritizing and organizing essential learning requirements within the institution to better serve students in the future. Valuable insights for scholars and academicians are presented, providing a foundational basis for future research and hypothesis generation. Additionally, the study underscores the significance of addressing the information needs of hospitality management students, urging prompt attention from government, institutions, and individuals to enhance the nation's education quality.